Arouna Bayoko Rural Economic Department (AMEDD) - Cinzana, Mali - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
In this video employee Arouna Bayoko describes the work of AMEDD, an NGO that works with groups of local farmers to help them adapt to climate change through the dissemination of adapted seed varieties and reforestation together with regulating firewood use.